Perbandingan Sistem Pendidikan Agama Islam di Indonesia dan Malaysia: Kajian Kurikulum dan Implementasinya di Sekolah Menengah - Ryanda Zuhri; Hesti Sulastri; Reva Ayunda Melki; Tiara Dwi Putri; Aprizal Ahmad (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study compares the Islamic religious education systems in Indonesia and Malaysia with a particular focus on curriculum design and its implementation within secondary schools. Using a qualitative research approach, data were gathered through document analysis and interviews with educators and school administrators from both countries. The findings show that although Indonesia and Malaysia share similar objectives in fostering students’ understanding and practice of Islamic teachings, several significant differences remain in terms of curriculum structure, learning materials, and instructional strategies. In Indonesia, Islamic religious education is more closely integrated into the national curriculum, emphasizing a balance between religious values and general educational competencies. Meanwhile, Malaysia adopts a more specific and traditionally oriented curriculum that places stronger emphasis on classical Islamic knowledge and conventional pedagogical practices. Implementation in both countries is shaped by government policies, socio-cultural contexts, and local wisdom that influence how Islamic education is delivered in the classroom. Overall, this study is expected to contribute as a useful reference for enhancing the effectiveness, relevance, and contextualization of Islamic education systems in both nations.